Kouno Fumiyo’s Hiroshima Manga: A Style-Centered Attempt at Re-reading - Miho, Takeuchi (Archīum Ateneo, 2024)
Kouno Fumiyo’s graphic narratives about Hiroshima, beginning with Yūnagi no machi, sakura no kuni (Town of Evening Calm, Country of Cherry Blossoms, 2004), have drawn attention as a new kind of A-bomb manga, but they have also met with harsh criticism by historians who privilege story and representational content when approaching manga. Against their charge of a lack of criticality, this review article highlights the critical potential of Kouno’s graphic narratives by focusing on how comics-specific style, especially paneling and linework, affects both narrative content and the act of reading. Kouno’s works exhibit a number of pecularities, ranging from what is drawn inside individual panels to the materiality of the line work marked, among other things, by the motif of the hand. The article demonstrates how these stylistic contrivances prompt not only re-reading, or revisiting both specific manga images and the represented past, but that they also allow for ‘touching’ the past. With respect to the latter, the article maintains, that Kouno’s manga promote a bodily kind of historical memory that implies an alternative to the exclusive concentration on thematic representation and ideological content. With respect to manga, the article emphasizes that critical potential arises to a significant extent from specific acts of reading facilitated by specific stylistic means.